STRATEGI BERSAING DALAM MELEWATI PADEMI COVID-19 (STUDI KASUS UMKM JAJANAN ENDOLITA KABUPATEN DEMAK) - Sulistyorini, Sulistyorini; Rizkiana, Citra; Kusumawati, Citra Andriani (Fakultas Ekonomi, Universitas Semarang, 2022)
AbstractThe purpose of this study was to determine the strategies used by UMKM endolita snacks, what competitive strategy is used during the pandemic so that it can compete until now. The research was conducted on UMKM endolita snacks in Demak. Methods of data collection is done by observation and interviews. The results showed that the competitive strategy carried out by endolita snack UMKM was a competitive strategy through SWOT analysis, strategy with a price (low cost), perform product differentiation by providing various kinds of snacks which are self produced and taken from distributors as well as products for sale. The conclusion of this study is that endolita snacks SMEs apply low-cost competitive and development of mission, objectives, strategies and policies so that they can be achievedthrough a SWOT analysis strategies and differentiation in increasing their competitiveness,to find strategic fit between external opportunities and internal strengths,in addition to paying attention to external threats and internal weaknesses.Keywords: covid-19, competitive strategy, SWOT, low cost, product differentiation.